2019
DOI: 10.1021/acs.est.8b05359
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Chemical Transformation in Biomass Burning Plumes: A Box Model Analysis Initialized with Aircraft Observations

Abstract: Biomass burning (BB) is a large source of reactive compounds in the atmosphere. While the daytime photochemistry of BB emissions has been studied in some detail, there has been little focus on nighttime reactions despite the potential for substantial oxidative and heterogeneous chemistry. Here, we present the first analysis of nighttime aircraft intercepts of agricultural BB plumes using observations from the NOAA WP-3D aircraft during the 2013 Southeast Nexus (SENEX) campaign. We use these observations in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 83 publications
4
140
0
Order By: Relevance
“…15 As a result, I/SVOCs from domestic solid fuel combustion potentially represent a large global source of SOA, however, the effect of I/SVOCs on OH reactivity, aging and SOA formation remains poorly understood. [16][17][18] The factors controlling SOA formation are complex. These include the oxidation of NMVOCs to less volatile products which partition into the particle phase, the heterogeneous oxidation of particle-phase SVOCs, and plume dilution with subsequent SVOC evaporation followed by further gas-phase oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…15 As a result, I/SVOCs from domestic solid fuel combustion potentially represent a large global source of SOA, however, the effect of I/SVOCs on OH reactivity, aging and SOA formation remains poorly understood. [16][17][18] The factors controlling SOA formation are complex. These include the oxidation of NMVOCs to less volatile products which partition into the particle phase, the heterogeneous oxidation of particle-phase SVOCs, and plume dilution with subsequent SVOC evaporation followed by further gas-phase oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary transformation of precursors was another source of ambient BrC. NO 3 , amines, and ammonium sulfate‐mediated transformation produces strong light‐absorbing BrC (Decker et al, 2019; Jiang et al, 2019; Powelson et al, 2013). Secondary BrC formed by direct photolysis and OH oxidation is photobleaching (Zhao, Lee, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Large emissions of furanic species were measured from fuel wood (6-59 %), municipal solid waste (35-45 %), cow dung cake (39-42 %), crop residue (25-44 %) and sawdust (43 %). These were important as furans can be toxic and mutagenic (Ravindranath et al, 1984;Peterson, 2006;Monien et al, 2011;WHO, 2016) and have been shown to be some of the species with the highest OH reactivity from biomass burning emissions (Hartikainen et al, 2018;Coggon et al, 2019). Furans have also been shown to result in SOA production (Gómez Alvarez et al, 2009;Strollo and Ziemann, 2013) with 8-15 % of SOA produced from combustion of black spruce, cut grass, Indonesian peat and ponderosa pine estimated to originate from furans and 28-50 % of SOA from rice straw and wiregrass (Hatch et al, 2015).…”
Section: Total Identificationmentioning
confidence: 99%
“…However, the effect of atmospheric of aging on I/SVOCs still remains poorly understood (Liu et al, 2017;Decker et al, 2019;Sengupta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%